Viral Marketing, Karakteristik Konsumen, Karakteristik Produk, Kepercayaan Pelanggan dan Keputusan Pembelian Online - Philia Magdalena Effendie; IGN Putra Suryanata (Universitas Pendidikan Nasional, 2018)
ABSTRACT The research objective to be achieved is the influence of viral marketing, consumer characteristics, product characteristics to customer trust and online purchasing decisions. The population of this research were students of Undiknas Denpasar who had been online purchased and the sample of this research was taken as many as 100 people. This sample is taken by Accidental Sampling technique. Data analysis using Structured Equation Model (SEM). The results of this research indicate that there is a positive and significant influence between viral marketing, consumer characteristics and product characteristics to customer trust and online purchasing decisions. Similarly, customer trust has a positive and significant impact on online purchasing decisions.